The Role of Green Spaces in Supporting Physical Activity and Functional Rehabilitation in Older Adults: A Scoping Review - Adelia Suryani; Sri Gunda Fahriana Fahruddin; Annisa Putri S (Journal of Public Health for Tropical and Coastal Region, 2026)
Introduction: Healthcare systems are under increasing strain owing to the rapid growth of the global aging population, underscoring the urgent need for environments that support healthy aging. Green open spaces (GOS) are increasingly recognized as vital infrastructure capable of mitigating age-related functional decline.Methods: This scoping review systematically synthesized evidence on the impact of green open spaces (GOS) in promoting physical activity (PA) and supporting functional rehabilitation among older adults. Guided by the Population, Concept, and Context (PCC) framework, a structured search was conducted across the Google Scholar, PubMed, and Scopus databases. Of the records initially identified, ten articles published between 2015 and 2025 were included in the final synthesis.Results: The findings indicate that green open spaces (GOS) support four primary dimensions of rehabilitation: physical (38%), psychological (31%), social (25%), and spiritual (6%). Furthermore, the influence of GOS design on physical activity (PA) can be categorized into gentle, simple movements (40%), moderate-intensity exercises (30%), and nature-integrated therapeutic activities (30%).Conclusion: Optimizing the benefits of green open spaces (GOS) for older adults requires attention to modifiable design features, universal accessibility (e.g., even terrain and adequate seating), and adaptation to local climatic and social contexts.